Implementation of the Language Skills Development in Online Learning in Jelita Silau Dunia Kindergarten, Serdang Bedagai Regency, North Sumatra Province - Anggi Fahira; Izzati Izzati (Universitas Pendidikan Indonesia Kampus Serang, 2021)
One aspect of early childhood development that must be stimulated from an early age is language skills. Language skills play an essential role for children in communication to convey messages to one another. However, at this time, the development of children's language skills is not optimally stimulated due to the COVID-19 pandemic, which has resulted in the learning process being carried out online. Previously, the learning process for early childhood was carried out face-to-face, but during this pandemic, learning is done online. It is influential on the growth and development of early childhood, especially children's language. Thus, this study aims to describe how the implementation of language skills development in online learning in Jelita Silau Dunia Kindergarten, Bintang Bayu Sub-district, Serdang Bedagai Regency, North Sumatra. The method used was descriptive analysis research, employing a qualitative approach, carried out at the Jelita Silau Dunia Kindergarten from April to June 2021. Based on the initial observations made at the Jelita Silau Dunia Kindergarten, the researchers saw that many children had developed their language skills. The results of this study revealed that during the pandemic, the implementation of language skills development in online learning at Jelita Silau Dunia Kindergarten continued as expected. Even though the learning process was carried out alternately online and offline, the teacher still stimulated the development of language skills well. The methods and media utilized by teachers varied so that children did not feel bored when carrying out learning activities during the pandemic.